OVERCOMING BARRIERS TO EMPLOYMENT: STRATEGIES FOR ENHANCING JOB SEARCH SKILLS AMONG TVET ESL GRADUATES - Nor Rulmaisura Mohamad; Nurul Ajleaa Abdul Rahman; Goh Ying Soon (Journal of Islamic, Social, Economics and Development, 2024)
This research delves into the employment challenges encountered by graduates of Technical and Vocational Education and Training (TVET) programs, with a special emphasis on the hurdles they face in crafting persuasive cover letters and resumes, as well as in mastering the intricacies of job interviews. Utilizing a comprehensive mixed-methods approach that amalgamates the quantitative clarity of surveys with the depth of qualitative interviews, this study draws on the experiences of TVET graduates to shed light on the multifaceted nature of job-seeking difficulties. The findings reveal that a significant number of graduates struggle with articulating their skills and experiences in written application materials and exhibit considerable anxiety and lack of preparation in interview settings. These challenges are further compounded by issues of language proficiency and self-confidence, underscoring the need for targeted support and training. By offering actionable recommendations for educators, career counsellors, and policy makers, this paper advocates for the integration of specialized training modules and workshops aimed at bolstering the job search efficacy of TVET graduates. The goal is to equip these individuals with the necessary tools to navigate the competitive job market successfully, thereby enhancing their prospects for securing employment that aligns with their training and aspirations.